Catholic revival in the age of the baroque religious identity in southwest Germany, 1550-1750 - Forster, Marc R. (Cambridge University Press, 2001)
This book is a study of Catholic reform, popular Catholicism and the development of confessional identity in southwest Germany. Based on extensive archival study, it argues that Catholic confessional identity developed primarily from the identification of villagers and townspeople with the practices of Baroque Catholicism - particularly pilgrimages, processions, confraternities and the Mass. Thus the book is in part a critique of the confessionalization thesis which dominates scholarship in this field. The book is not however focused narrowly on the concerns of German historians. An analysis of popular religious practice and of the relationship between parishioners and the clergy in villages and small towns allows for a broader understanding of popular Catholicism, especially in the period after 1650. Local Baroque Catholicism was ultimately a successful convergence of popular and elite, lay and clerical elements, which led to an increasingly elaborate religious style
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Katholische Kirche; Catholic Church / Germany, Southern / History / 16th century; Catholic Church / Germany, Southern / History / 17th century; Catholic Church / Germany, Southern / History / 18th century; Geschichte 1700-1800; Geschichte 1600-1700; Geschichte 1500-1600; Geschichte 1550-1750; Geschichte; Kirchengeschichte; Katholische Erneuerung; Volksfrömmigkeit; Katholizismus; Germany, Southern / Church history / 16th century; Germany, Southern / Church history / 17th century; Germany, Southern / Church history / 18th century; Südwestdeutschland